2012
DOI: 10.1117/1.jbo.17.11.116017
|View full text |Cite
|
Sign up to set email alerts
|

Collagen I fiber density increases in lymph node positive breast cancers: pilot study

Abstract: Abstract. Collagen I (Col1) fibers are a major structural component in the extracellular matrix of human breast cancers. In a preliminary pilot study, we explored the link between Col1 fiber density in primary human breast cancers and the occurrence of lymph node metastasis. Col1 fibers were detected by second harmonic generation (SHG) microscopy in primary human breast cancers from patients presenting with lymph node metastasis (LN þ ) versus those without lymph node metastasis (LN − ). Col1 fiber density, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 47 publications
(85 reference statements)
10
81
0
2
Order By: Relevance
“…46 A high density of collagen 1 fibers in the ECM has been identified as a predictor of increased metastasis. 47,48 High collagen density has also been observed to increase tractions by breast cancer cells. 43 Increased metastasis associated with high collagen density may be mediated in part by this increased tractions.…”
Section: Discussionmentioning
confidence: 99%
“…46 A high density of collagen 1 fibers in the ECM has been identified as a predictor of increased metastasis. 47,48 High collagen density has also been observed to increase tractions by breast cancer cells. 43 Increased metastasis associated with high collagen density may be mediated in part by this increased tractions.…”
Section: Discussionmentioning
confidence: 99%
“…3 Mechanistically, it is hypothesized that aligned collagen fibers form pathways that facilitate cancer cell migration away from the tumor and toward vasculature during the metastatic process. 3,4 While there is significant research work ongoing on the role of collagen in live, dynamic in vitro and in vivo animal models of a wide array of cancers, [5][6][7][8][9][10] many groups, including ours, are also focused on investigating the potential clinical utility of collagen properties in routinely fixed and processed human tissues. Toward clinical translation, it has already been shown that the detection of TACS in routine histopathological evaluation of breast cancer can serve as an optical biomarker and be predictive of disease recurrence and patient survival.…”
Section: Research-article2016mentioning
confidence: 99%
“…It has been demonstrated that fixation does not alter the underlying fibrillar collagen structure and the resulting SHG properties [36][37][38] and primarily results in a slight volumetric shrinking. 39 For imaging, a single fascicle was pulled from the tail, and a small section was cut lengthwise, placed on a microscope slide with a drop of PBS, and sealed with a coverslip using nail polish (Sinful Colors).…”
Section: Specimens and Preparationmentioning
confidence: 99%